2005
DOI: 10.1590/s1516-35982005000600001
|View full text |Cite
|
Sign up to set email alerts
|

Proteína bruta e energia digestível em dietas para alevinos de curimbatá (Prochilodus affins)

Abstract: RESUMO -Objetivando-se determinar as exigências de proteína bruta (PB) em função do nível de energia digestível (ED) da dieta para alevinos de curimbatá (Prochilodus affins), foram utilizados 256 peixes com peso inicial de 2,72 ± 0,11 g, mantidos em 32 aquários de 100 L, dotados de abastecimento de água, temperatura controlada e aeração individuais. O experimento foi realizado seguindo-se esquema fatorial 4 x 2 (quatro níveis de PB: 18,0; 22,0; 26,0; e 30,0%, combinados com dois níveis de ED: 2.700 e 3.000 kca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
10
3
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 26 publications
7
10
3
16
Order By: Relevance
“…The response fitted to the LRP model in the present study was consistent with that observed by Bomfim et al (2005), who reported a linear increase in WG in "curimbatá" (Prochilodus affinis) fingerlings, and the occurrence of a plateau at one of the intermediate CP levels evaluated. In contrast, the present results differ from those obtained by Vidal Júnior et al (1998), who found a quadratic effect on weight gain, with variations in dietary protein levels in tambaquis weighing 30-250 g.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The response fitted to the LRP model in the present study was consistent with that observed by Bomfim et al (2005), who reported a linear increase in WG in "curimbatá" (Prochilodus affinis) fingerlings, and the occurrence of a plateau at one of the intermediate CP levels evaluated. In contrast, the present results differ from those obtained by Vidal Júnior et al (1998), who found a quadratic effect on weight gain, with variations in dietary protein levels in tambaquis weighing 30-250 g.…”
Section: Resultssupporting
confidence: 90%
“…In contrast, Bomfim et al (2005) and Cotan et al (2006) have shown lower moisture levels in "curimbatá" fingerlings and "lambari tambiú" fingerlings, respectively, that were fed diets comprising relatively low levels of CP, compared to those fed higher levels of CP. Body fat levels decreased in a quadratic manner (to yield a minimum value of 2.36%), until an estimated CP level of 26.55% was achieved (Table 3).…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations